2010
DOI: 10.1161/atvbaha.110.216531
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Procoagulant Platelets

Abstract: Objective To define and characterize the subpopulation of platelets capable of regulating the functional interactions of factors Va (FVa) and Xa (FXa) on the thrombin-activated platelet surface. Methods and Results Flow cytometric analyses were used to define and characterize platelet subpopulations. At a concentration of thrombin known to elicit maximal platelet activation, platelet-derived FVa release, and prothrombinase assembly/function, only a subpopulation of platelets were positive for FVa and FXa bin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(24 citation statements)
references
References 32 publications
3
20
0
Order By: Relevance
“…11 In vitro flow experiments identified superactivated platelets after adhesion to collagen matrices as well, suggesting that collagen alone, perhaps in combination with shear stress, may be sufficient to produce this platelet phenotype. 7 Similarly, Fager et al 12 showed that high concentration of thrombin is sufficient to generate superactivated platelets in comparable proportions and with comparable procoagulant activity to platelets activated by thrombin and convulxin. Stimulation with thrombin coupled with an activator of the platelet Fc Receptor, FcγRIIA, similarly generates a population of superactivated platelets (although it was also noted that this agonist combination consistently produced a smaller proportion of superactivated platelets than stimulation with collagen and thrombin).…”
Section: Properties Of Superactivated Plateletsmentioning
confidence: 98%
See 2 more Smart Citations
“…11 In vitro flow experiments identified superactivated platelets after adhesion to collagen matrices as well, suggesting that collagen alone, perhaps in combination with shear stress, may be sufficient to produce this platelet phenotype. 7 Similarly, Fager et al 12 showed that high concentration of thrombin is sufficient to generate superactivated platelets in comparable proportions and with comparable procoagulant activity to platelets activated by thrombin and convulxin. Stimulation with thrombin coupled with an activator of the platelet Fc Receptor, FcγRIIA, similarly generates a population of superactivated platelets (although it was also noted that this agonist combination consistently produced a smaller proportion of superactivated platelets than stimulation with collagen and thrombin).…”
Section: Properties Of Superactivated Plateletsmentioning
confidence: 98%
“…However, there may be more than higher levels of PS exposure to account for enhanced binding of FVa to the membrane surface. It was noted by Fager et al 12 that when superactivated platelets were washed, a significant amount of platelet-derived FVa could not be removed from the platelet surface, leading the authors to conclude that FVa was tethered to the membrane surface by the heavy chain of the cofactor that was bound to the surface, potentially through a glycosylphophtidylinositol anchor. An alternative hypothesis was proposed by Dale et al, 26 which was based on the observation that not only was FVa bound on the platelets' surface but there was retention of other α-granule contents as well, including von Willebrand factor, fibrinogen, and thrombospondin, and therefore described the superactivated platelets as coated.…”
Section: Properties Of Superactivated Plateletsmentioning
confidence: 99%
See 1 more Smart Citation
“…The population of circulating platelets is not homogeneous [33], immature platelets comprise the youngest component of the circulating platelet pool, and appear to participate most actively in the thrombotic process [34]. They contain measurable amounts of cytosolic messenger ribonucleic acid (mRNA) that is translationally active [35].…”
Section: The "Fiction Of the Perpetually Platelet Inactivation"mentioning
confidence: 99%
“…Flow cytometric analysis of PS‐exposing platelets in suspension using fluorescently‐labeled annexin A5, first described over two decades ago,20 has become widely used in studies of procoagulant platelets and platelet‐derived extracellular vesicles (EVs) 4, 21, 22, 23, 24, 25. A limitation of traditional flow cytometry is the lack of images of individual analyzed cells.…”
Section: Introductionmentioning
confidence: 99%